Near-Bed Current Velocity Profiles in The Eastern Irish Sea: Implications for Radioactive Waste Disposal - Rehman, Syed Shafiqur (Journal of Himalayan Earth Sciences, 1991)
Near-bed current velocity data have been recorded at six different stations in the eastern Irish Sea using a vertical array of five electromagnetic current meters in the boundary layer. The data suggests that circulation in the Irish Sea is dominated by tidal streams modulating at semi-diurnal frequency and circulating in counter-clockwise direction. Values of friction velocity and roughness height determined from the current velocity suggest that (1) for slow currents the flow is “smooth turbulent” in most part, (2) at higher velocities the flow becomes "rough turbulent" and the seabed becomes rippled. It appears that form drag increases resistance to flow instead of skin friction (grain size). Wave parameters recorded at one of the stations indicate that during calm weather wave height varied between 11.4 cm to 1.11 m, wave period between 8-20 S, and wavelength from 103 to 346 m in 35 m deep water. It has also been observed that even in the presence of small waves, wave orbital currents are produced in the boundary layer which add to the shear stress caused by tidal currents and increase the potential for resuspension of bed sediments. Since the Irish Sea generally becomes storm dominated during winters, resuspension of bed sediments and attached radionuclides may increase during this season.